Remote laboratory VISIR: recent advances, initiatives, federation, limitations and future - Garcia-Loro, Felix (2021)
This document reflects the contribution of a group of experts in the VISIR (Virtual Instrument Systems in Reality) remote lab, regarding recent advances, initiatives, federation, limitations and future. The methodology for gathering their opinion consisted of a SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis on VISIR, following three categories: Technical, Pedagogical and Educational. Major conclusions point to: (1) a need for new technical developments taking advantage of collaborative work; (2) a window of opportunity for expanding VISIR to other institutions, namely in developing countries; and (3) improving the interface for a better pedagogical experience, namely with better error feedback or the inclusion of a virtual tutor.